INCIDENCE OF KIDNEY STONES IN KIDNEY TRANSPLANT RECIPIENTS - MANAN , FE; REHMAN , KU; ULLAH , I; SHAHINDA, DR (Biological and Clinical Sciences Research Journal, 2024)
The incidence of kidney stones in kidney transplant recipients is a significant concern within the realm of post-transplant complications. The study’s main objective is to find the incidence of kidney stones in kidney transplant recipients. This retrospective study was conducted at the Institute of Kidney Diseases Peshawar from 2017 to 2023. Data was collected from 420 kidney transplant patients. All patients above 18 years with available medical records who underwent renal transplants in IKD and outside IKD and who presented to IKD for follow-up were included in the study—patients with a history of kidney stones before the transplant process were excluded. Demographic information, including age, gender, and pre-transplant comorbidities, was recorded for each patient. Data were collected from 420 patients with kidney transplants. Out of 420 patients, 35 patients developed kidney stones after transplantation. The mean age of the patients who developed stones was 48.7 ± 10.2 years. There were 45.7% male and 54.3% female patients in the kidney stone group. 25.7% of patients had pre-transplant DM. Most kidney stones analyzed in the study comprised calcium oxalate, representing 18 cases, followed by calcium phosphate with eight instances. The correlation analysis revealed that age and gender did not significantly correlate with kidney stone formation in transplant patients, with p-values of 0.32 and 0.17, respectively. It is concluded that kidney transplant recipients exhibit a notable incidence of kidney stone formation, with tacrolimus-based immunosuppressive regimens potentially contributing to this risk. While age and pre-transplant diabetes show trends toward association with kidney stone development.